(untitled) (Journal of Imam Al-Kadhim College, 2025)
The Holy Qur’an is a primary source of guidance and purification, and it has formed a vital spiritual and scientific source in the building of Islamic civilization. Educational and spiritual meanings have branched out from its verses and are still present in contemporary Islamic thought. The noble prophetic traditions and narrations from the Ahl al-Bayt (peace be upon them) urged believers to recite the Qur’an, ponder its meanings, and reflect on its purposes. This call formed an important interpretive background that helped interpreters delve into the educational and social dimensions of the verses and chapters, taking into account the objectives of revelation according to the stages of revelation and the different nature of the Meccan and Medinan chapters. In light of this prophetic and Ahlulbayt guidance, serious attempts emerged to define the objectives of the surahs and distinguish their characteristics according to the contexts of their revelation. Advanced exegetical studies have demonstrated that the idea of distinguishing between Meccan and Medinan surahs was not foreign to the scholarly atmosphere of early Islam; rather, the Prophet (peace be upon him) and the Imams of his household (peace be upon them) adopted it in explaining the purposes of Islamic law and the methods of calling to Islam. Thus, semantic divisions emerged, aiming to highlight the specific character of each group of surahs and define their message within the overall Quranic framework. The study adopted an Analytical inductive approach based on reliable interpretive sources and available digital records, while following a descriptive analytical approach aimed at exploring the educational structure in the chapters of the Holy Qur’an through a selected interpretive record represented by the interpretations of Majma’ al-Bayan by Allamah al-Tabarsi and Al-Mizan fi Tafsir al-Qur’an by Allamah al-Tabataba’i, because they are among the most prominent interpretations that combined transmission and reason, and the apparent and the hidden in a comprehensive systematic way.